PERANCANGAN PEMBUATAN VIDEO DAUR ULANG BAN KENDARAAN MENGGUNAKAN AUGMENTED REALITY DENGAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Anggara, Kevin; Simanjuntak, Pastima (LPPM Universitas Putera Batam, 2022)
Tires are a component of two-wheeled and four-wheeled vehicles, such as cars, motorcycles, and bicycles. Tires have a role that is so that the vehicle can move. Tires can also be used to reduce vibration caused by road irregularities, protecting the wheels in a vehicle from damaged or uneven roads. Some vehicle tires can be damaged or punctured if they hit a sharp object such as a nail or thorn. In addition to being exposed to sharp objects, vehicle tires can also thin out if the tires are used for very long time, so it can no longer be used on any vehicle. Therefore, vehicle tires that are not suitable for use can be reused by recycling, one example is being used as plant pots. Therefore, vehicle tires that are not suitable for use can be reused by recycling, one example is being used as plant pots. So with that, researchers will create a software that can explain a way to recycle vehicle tires into plant pots with software, namely Augmented Reality. To design and implement a video of vehicle tire recycling using Augmented Reality with the Multimedia Development Life Cycle method. The method of the Multimedia Development Life Cycle consists of 6 stages, namely Concept, Design, Material Collection, Presentation, Experiment, and Distribution. The result of the end of this research is a video in the form of Augmented Reality to learn how to recycle vehicle tires into plant pots in the form of Augmented Reality